Haptic experience design: What hapticians do and where they need help. Issue 107 (November 2017) - Schneider, Oliver; MacLean, Karon; Swindells, Colin; Booth, Kellogg
Abstract: From simple vibrations to roles in complex multisensory systems, haptic technology is often a critical, expected component of user experience – one face of the rapid progression towards blended physical-digital interfaces. Haptic experience design, which is woven together with other multisensory design efforts, interfaces is now becoming part of many designers' jobs. We can expect it to present unique challenges, and yet we know almost nothing of what it looks like "in the wild" due to the field's relative youth, its technical complexity, the multisensory interactions between haptics, sight, and sound, and the difficulty of accessing practitioners in professional and proprietary environments. In this paper, we analyze interviews with six professional haptic designers to document and articulate haptic experience design by observing designers' goals and processes and finding themes at three levels of scope: the multisensory nature of haptic experiences, a map of the collaborative ecosystem, and the cultural context of haptics. Our findings are augmented by feedback obtained in a recent design workshop at an international haptics conference. We find that haptic designers follow a familiar design process, but face specific challenges when working with haptics. We capture and summarize these challenges, make concrete recommendations to conquer them, and present a vision for the future of haptic experience design.